Pelo gramofone: a cultura da gravação e a sonoridade do samba (1917-1971) - Marcos Edson Cardoso Filho (2008)
The possibilities of sound recording and reproduction, introduced by Thomas Edisons phonograph, brought significant changes in the way people produce and listen to music. In Brazil, the commercial recordings began in 1902 and, since then, the practices of popular music main product of the recording industry had to adapt themselves to the recording culture. From the dialogue between recording technologies and the brazilian popular music emanated many different sonorities and these aided to structure the popular song language. The present study investigates the phonographic practices in Brazil and their relationship with the changes of sonority in the recorded samba. Starting from the belief that technology influences the aesthetics and the language of the recorded popular music, our goal is to discover and describe how that influence occurs. The research includes two eras: the acoustic and electric ages of recording (until 1971). The first part of the work is a historical discussion of the record culture in Brazil and its studio practices. For that, semi-structured interviews were used withsingers and researchers, along with the reading of primary sources (texts about recorded music published in the studied periods). In the second part, aural and sonological analyses of sambas are proposed with special attention to Mario Reis phonography.